Anatomy and Physiology of Water Buffalo Mammary Glands: An Anatomofunctional Comparison with Dairy Cattle - Mota Rojas, Daniel (2024)
The present review aims to analyze the anatomical and physiological characteristics of the mammary gland and udders of water buffalo by making an anatomofunctional comparison with dairy cattle. It will also discuss the knowledge generated around the physiological regulation of milk ejection in the water buffalo. It was found that buffalo's average udder depth and width is approximately 20 cm smaller than Bos cattle. One of the main differences with dairy cattle is a longer teat canal length (around 8.25-11.56 cm), which highly influences buffalo milking. In this sense, a narrower teat canal (2.71 ± 0.10 cm) and thicker sphincter muscle are associated with needing higher vacuum levels when using machine milking in buffalo. Moreover, the predominant alveolar fraction of water buffalo storing 90-95% of the entire milk production is another element that can be related to the lower milk yields in buffalo (when compared to Bos cattle) and the requirements for prolonged prestimulation in this species. Considering the anatomical characteristics of water buffalo's udder could help improve bubaline dairy systems.